The Differential Complex Equation Pu = f: A Solution Using the Kernel Method (المجلة الدولية للبحوث العلمية, 2026)
In this study, a general approach to solving partial differential equations in what are called "differential complexes." The method is based on the main principle of breaking the equation's basic answer into two parts. This decomposition makes it possible to establish the criteria required for the existence of solutions as well as to create explicit formulas for solutions, making it a potent and adaptable tool that goes beyond the constraints of conventional approaches.